2015
DOI: 10.3109/19390211.2015.1107802
|View full text |Cite
|
Sign up to set email alerts
|

6-Gingerol-Rich Fraction fromZingiber officinalePrevents Hematotoxicity and Oxidative Damage in Kidney and Liver of Rats Exposed to Carbendazim

Abstract: Ginger (Zingiber officinale) is a globally marketed flavoring agent and cooking spice with a long history of human health benefits. The fungicide carbendazim (CBZ) is often detected in fruits and vegetables for human nutrition and has been reported to elicit toxic effects in different experimental animal models. The present study investigated the protective effects of 6-Gingerol-rich fraction (6-GRF) from ginger on hematotoxicity and hepatorenal damage in rats exposed to CBZ. CBZ was administered at a dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Pups in the control group (21% O 2 for 14 days + placebo) and hyperoxia + LPS group (95% O 2 for 14 days + placebo) were administered oral saline (2 mL/kg), but pups in the hyperoxia + LPS + ginger group (95% O 2 for 14 days + ginger) were treated once a day from the first day of the study to the end of the study. In the present experiment, we used whole ginger since many different compounds in ginger have been determined to act in a synergic manner that suggests the importance of using whole ginger (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Preparation and Dosage Of Gingermentioning
confidence: 99%
“…Pups in the control group (21% O 2 for 14 days + placebo) and hyperoxia + LPS group (95% O 2 for 14 days + placebo) were administered oral saline (2 mL/kg), but pups in the hyperoxia + LPS + ginger group (95% O 2 for 14 days + ginger) were treated once a day from the first day of the study to the end of the study. In the present experiment, we used whole ginger since many different compounds in ginger have been determined to act in a synergic manner that suggests the importance of using whole ginger (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Preparation and Dosage Of Gingermentioning
confidence: 99%
“…Previous studies demonstrated that CBZ induced testicular atrophy via sloughing of germ cells, inhibition of Sertoli cell microtubule function, induction of oxidative stress, apoptosis and DNA damage leading to infertility (Adedara, Vaithinathan, Jubendradass, Mathur, & Farombi, ; Aire, ; Bjørge et al., ; Salihu, Ajayi, Adedara, de Souza et al. ; Salihu, Ajayi, Adedara, & Farombi, ; Yu, Guo, Xie, Liu, & Wang, ). Thus, recent investigations are aimed at protecting human health involve the use of antioxidants and naturally occurring substances to mitigate or inhibit oxidant‐induced testicular damage due to excessive generation of free radicals from exposure to environmental contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Several herbal plants have been scientifically proven to possess pharmacological principles which make them useful as curatives for numerous ailments including infertility (D'Cruz, Vaithinathan, Jubendradass, & Mathur, ). Zingiber officinale, which is popularly known as ginger, is a globally marketed flavouring agent and cooking spice with a long history of human health benefits (Salihu et al., ). The focus on the human health benefits of ginger is on the increase due to its low toxicity and the presence of potent phytochemicals including gingerols, shogaols, zingerones and zingiberone (Salihu, Ajayi, Adedara, de Souza et al.…”
Section: Introductionmentioning
confidence: 99%
“…Group V rats orally were orally co‐treated with CBZ and 6‐GRF at 200 mg/kg (6‐GRF3). The dose of CBZ (50 mg/kg) was chosen from previously published study (WHO, ), whereas 50, 100 and 200 mg/kg 6‐GRF and the duration of treatment were selected from our preliminary studies (Salihu et al., ). Twenty‐four hours after the last treatment, the rats were sacrificed by cervical dislocation, and blood was collected from retro‐orbital venous plexus using heparin‐containing tubes.…”
Section: Methodsmentioning
confidence: 99%
“…6‐Gingerol (1‐[4′‐hydroxy‐3′‐methyoxyphenyl]‐5‐hydroxy‐3‐decanone is the most pungent of all the active principles found in ginger and has been shown to possess anticancer, anti‐inflammatory and antioxidant properties (Surh et al., ; Surh, ; El‐Ghorab, Nauman, Anjum, Hussain, & Nadeem, ; Dugasani et al., ; Salihu, Ajayi, Adedara, & Farombi, ). However, as one of the principal bioactive components in ginger, there is paucity of information on the influence of 6‐gingerol on CBZ‐induced reproductive toxicity.…”
Section: Introductionmentioning
confidence: 99%